What ophthalmologists need to know about pandemic of Corona Virus 19 - Elshimaa Mossa; Alahmady Hammad Alsmman (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or novel coronavirus 2019 (Covid19) is an emerging life-threatening catastrophe worldwide with no country immune from this problem. Ophthalmologists are in the first line facing this pandemic due to their intimate contact during clinical examination and surgery. Objective: Ophthalmologists should have base line of knowledge about Covid 19 and sources of infection and methods of transmission. Ophthalmologists have two lines in their practical life outpatient clinic line and surgical line. In this article we tried to help ophthalmologists all over the world to know basics about Covid 19 pandemic and how to deal to decrease risk of infection either in examination in out patient clinic and in operative rooms. Conclusion: Strong instruction should seriously be followed by ophthalmologists, nurses and workers in outpatient clinics and surgical centers to avoid infection, distance separation and avoiding unneeded exposure should respected. Lastly all health care should be available for any ophthalmologist or working in this field like regular nasopharyngeal flabs, isolation hospital or even intensive care units when needed as they are in first line facing this dangerous disease.